1997
DOI: 10.1038/bjc.1997.248
|View full text |Cite
|
Sign up to set email alerts
|

Isolated hepatic perfusion in the pig with TNF-alpha with and without melphalan

Abstract: Summary Isolated limb perfusion with tumour necrosis factor alpha (TNF-a) and melphalan is well tolerated and highly effective in irresectable sarcoma and melanoma. No data are available on isolated hepatic perfusion (IHP) with these drugs for irresectable hepatic malignancies. This study was undertaken to assess the feasibility of such an approach by analysing hepatic and systemic toxicity of IHP with TNF-a with and without melphalan in pigs. Ten healthy pigs underwent IHP. After vascular isolation of the liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
10
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
3
10
0
Order By: Relevance
“…All changes in serum enzyme levels had returned to normal at the end of the first postoperative week. Similar results are reported by Borel Rinkes et al [21]. Furthermore, in our control group enzyme levels revealed transient increases of transaminases and also a decrease of synthetic liver function (Quick test).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…All changes in serum enzyme levels had returned to normal at the end of the first postoperative week. Similar results are reported by Borel Rinkes et al [21]. Furthermore, in our control group enzyme levels revealed transient increases of transaminases and also a decrease of synthetic liver function (Quick test).…”
Section: Discussionsupporting
confidence: 79%
“…Thus, in our series a significant reduction of systemic human TNF· and pTNF· levels after reperfusion as well as of severe cardiopulmonary side effects could be achieved. Similarly, Borel Rinkes et al [21] did also not observe lethal complications of serum rhTNF· levels of 17 ! 10 3 pg/ml (17 ng/ml) after isolated liver perfusion in pigs with 50 Ìg rhTNF·/ kg BW.…”
Section: Discussionmentioning
confidence: 99%
“…These findings might be of clinical relevance in more than one way. First, it suggests that the very high doses used presently in the clinical setting may well be reduced while retaining efficacy, but even more importantly this observation increases the chances that TNF may become applicable in other settings such as isolated hepatic perfusions (Fraker et al, 1994;Borel Rinkes et al, 1997;Alexander et al, 1998;De Vries et al, 1998). These settings are clearly less ideal, due to local toxicity, than the setting of the 'inert' limb perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Different models have been developed to evaluate the efficacy of TNF-α in organ perfusion, such as in lung (Weksler et al, 1993(Weksler et al, , 1994Pogrebniak et al, 1994), and in liver (Fraker et al, 1994;Borel Rinkes et al, 1997). TNF-α in isolated lung perfusion has been shown to be safe, and in a phase I study tumour responses have been observed in patients with lung metastases (Pass et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Isolated singlelung perfusion with TNF-α proved to be safe (Pogrebniak et al, 1994;Weksler et al, 1994;Pass et al, 1996). Reports on the use of TNF-α in isolated liver perfusion at the National Cancer Institute in the USA (Fraker et al, 1994) as well as by our group (Borel Rinkes et al, 1997) have appeared very recently.…”
mentioning
confidence: 96%